The relationships between Orthorexia nervosa, social appearance anxiety and women’s self-esteem: A cross-sectional study - DURAN, Songül; Can ÖZ, Yüksel (Bangladesh Journal of Medical Science, 2022)
Objectives: It is known that eating disorders and desire to be thin are more common in women. It was also stated that social appearance anxiety and self-esteem in women may be associated with eating disorders. This study aimed to identify the relationships between Orthorexia nervosa, social appearance anxiety and women’s self-esteem. Material and methods: This descriptive cross-sectional study was conducted with 222 women. Results and Discussion: The study determined a mean score on the Orthorexia Scale. It determined that 27% of the women had orthorexic tendencies, and that the orthorexic tendencies of those who were worried about gaining weight were lower than those who were not worried about gaining weight. There was a negative and statistically significant relationship between the social appearance anxiety scale (SAAS) and the Rosenberg Self-Esteem Scale (RSES). Conclusion: Health professionals should be informed about Orthorexia nervosa. At-risk groups should undergo screening, necessary precautions should be taken, and the condition should be treated. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 675-681